Two Christian Funerary Stelae in the Magazine at Fustât (Old Cairo) - El Mesiry, Amer; Blumell, Lincoln (Chronique d’Égypte, 2023)
Abstract This article presents editions of two unpublished Christian funerary stelae from the storage magazine in Fustât (Old Cairo). One is written entirely in Coptic while the other is bilingual and is written in Greek and Coptic.